Do functional perturbations affect rotational knee joint kinematics? - Meinert, I.; Kingma, I.; Pijnappels, M. (ISBS - Conference Proceedings Archive (Konstanz), 2012)
The purpose of this study was the assessment of rotational knee joint kinematics following a functional perturbation. Perturbations were applied at different phases of the gait cycle with the subjects (n=18) running on a treadmill. During half of the trials a dual task was applied. A statistical comparison took place between strides with and without perturbations applied, showing significant differences. Therefore, the method presented in this study of the application of perturbations to mimic situations in which knee injuries are known to occur, resulted in changed rotational knee joint kinematics.